Trends in the Global and Ukrainian Markets of Cosmetics Products - Sviderska Svitlana Ye.; Kukhta Pavlo V. (Bìznes Inform, 2023)
The article aims at disclosing and summarizing the current trends in the development of cosmetics products markets, determining their volumes, dynamics and potential; analyzing the impact of global market conditions on the reactions of domestic players to crisis conditions. The research is relevant due to the peculiarities of the current conditions of development of the Ukrainian cosmetics products market. It is currently undergoing transformation due to government regulation affecting one of the largest market players. This opens up opportunities for small businesses, local and international investors to further develop, strengthen their market presence and attract additional investment. The methodological basis of this study is formed by general scientific methods, the complex combination and use of which made it possible to obtain important practical results. The cosmetics products markets, analyzed in the article, are defined as sustainable, stable-growing, and adaptive toward crisis occurrences. Overall, the industry that has undergone a transformation towards self-care, health and naturalness under the influence of the COVID-19 pandemic, accelerating the development of omnichannelness and innovations. Technological advances are crucial, influencing product development, customer interaction, marketing, etc. In particular, the development of e-commerce in the cosmetics products market is changing the way consumers think about the way they shop, facilitating the prior experience of finding the right product and providing the basis for more informed, yet faster, purchasing decisions. These facts are underlined by numerous statistical studies that support forecasts of the sustainability of development of e-commerce in this market in the future. In such circumstances, analyzing global trends in the cosmetics products industry helps to understand the dynamics of the local market and the behavior of players during crises. It is vital for local market players to adapt to global market rules and formulate effective strategies. It is summarized that, in addition to the generally recognized shifts in the cosmetics products market, such as the post-pandemic and the growth of e-commerce, it is important to consider trends that influence consumer choice and purchases, such as the need to personalize the consumer experience, the growth of the face and body care segment, the propensity to consume organic products, and the requirements for sustainable business development.